The first steps in professional training in Soviet Lithuania in 1919 - Mikėnas, V. (Psichologija, 1964)
Researching the issues has revealed that proletarian revolution, the establishment of the Soviet government, and the general organization of teaching in Lithuania were a direct consequence of the Great October Revolution.The Darbo Lietuva Newspaper (Labor Lithuania), headed by the Communist Party, took advantage of the experience of Soviet Russia and declared that training is related to employment and there is a principle of training unified professional school in Lithuania.Vocational training tasks were formulated in the spirit of the proletarian revolution, closely related to the political, economic, and cultural construction of socialism.Vocational training was regarded as part of the revolutionary struggle, an essential element of a holistic education of the younger generation.However, short-term existence the Soviet regime did not allow the implementation of these things.
Keywords: professional training and history of pedagogy.